THE ENGLISH SPEAKING SKILLS DEVELOPMENT OF MONDIAL SCHOOL KINDERGARTEN CHILDREN (Universitas Negeri Semarang, 2012)
Studi ini berkaitan dengan perkembangan bahasa pada siswa Modial Kindergarten dengan mempertimbangkan beberapa aspek kemampuan alami dan pengingat siswa yang membantu untuk mempelajari Bahasa Inggris. Data diperoleh melalui rekaman siswa saat pembelajaran di kelas. Setelah dikoleksi, data dianalisa dengan mentranskrip ekaman berdasar urutan dan menginterpretasikan untuk mengetahui perkembangan bahasa anak. Temuan studi menyarankan bahwaanak-anak dan dewasa bukan patner yang ideal dalam conversation. Hasil menunjukan bahwa anak-anak menggunakan bahasa scara kreatif, mereka bereksperimen dengan bahasa yang terpikir dalam kepala mereka secara tidak sadar yang mnunjukan bahwa siswa tidak hanya bereksperimen dengan bahasa tapi juga memmbutuhkan feedback untuk mengkonfirmasi hipotesis mereka.This study deals with the language development of Mondial kindergarten learners of English by considering some of the natural abilities and characteristics children possess which help them to learn English as a foreign language. The data is collected by recording the students’ utterances during several learning experiences and activities in the classroom. The data collected is then analyzed by transcribing those utterances based on turn and move before identifying and interpreting them to reveal the children’s English language development. The findings of this study suggest that adults and children are not equal conversation partners. In the beginning, adults do most of the talking during pretend plays and other activities. But as children develop greater control over language structures and vocabulary, they also play a bigger role in initiating and maintaining interaction. The data shows that children use language creatively. Students try to experiment and work out the rules of the language in their heads, though they may not be aware of doing this. One implication is that children need opportunities to try out and experiment with language, but they also need feedback to confirm or modify their hypothesis.